SIKAP MASYARAKAT DAN PERSEPSI TENTANG PERILAKU APARATUR TERHADAP MINAT MEMBUAT AKTA TANAH DI KECAMATAN SERANG - Ade Duwi Suryatna; Rd Nia Kania Kurniawati; Agus Sjafari (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2019)
Many people believe that they only have Land and Building Tax (SPPT-PBB) Tax Returns and that their land is legally enforceable. SPPT-PBB is a substitute form for Girik which is no longer recognized after the birth of the Basic Agrarian Law (UUPA). Therefore some of the problems that have been explained do indeed require the activities of making land certificates in order to have land rights with legal force. However, the community considered that to obtain the land certificate was very difficult, took a long time and required very expensive fees. Therefore, the writer wants to follow up on the problem and test it using theory and analyze it quantitatively with the aim of finding the influence of